Analysis of Ethical and Moral Values in Upin and Ipin Children’s Cartoon Film on Students’ Character Development - Najwa, Adinda; Ulfa Barus, Khairu (International Journal of Students Education, 2023)
Education in general is a process of learning and developing knowledge, skills, attitudes and moral values which is carried out systematically, structured and directed, both through formal learning in educational institutions, as well as through experience and interaction in the social environment. Education also has a role in forming attitudes, character and courage in facing life’s changes and challenges. The aim of education is to develop individual potential and prepare them to face roles and responsibilities in society. Character is a very important thing to form and develop in individuals, especially in children from an early age. This research aims to analyze and observe changes in character values due to the influence of the film Upin and Ipin in everyday life. Character education can be studied through various sources, one of which is visual media, namely films or cartoon series. The influence of entertainment media, especially films, cannot be considered trivial. Films can attract the attention of the audience to always watch, so that films can be used as a medium for learning material, therefore as a good observer you must be able to take positive values from watching films to emulate and put aside the negative values from films. The type of research used in this research is qualitative research with modeling effect research mechanisms (providing impressions), library research (collecting various kinds of reference reading), and eliciting effects (observing and observing). Based on the results of the analysis, it can be concluded that the influence of the film Upin and Ipin includes three character values, namely character values with an attitude of helping, friendship and politeness. Based on the results of this research, it can also be concluded that the children’s cartoon film Upin and Ipin is suitable for broadcasting to provide learning in a fun way for students.